KONTRIBUSI USAHA TANAMAN PERKEBUNAN BAGI PETANI MISKIN DI KABUPATEN TEMANGGUNG - Agus Hermawan; Sarjana Sarjana; Abdul Choliq; Forita Dyah Arianti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
Since last four years, area harvested and production of tobacco in Temanggung District tended to decrease due to the low price of tobacco. It forces farmers to search alternative commodities. Survey to find out the role of estate crops for poor farmers was carried out in September-October 2004 inTernanggung District. The assessment involved 91 farmers who coming from three sub districts, i.e. Pringsurat Sub District (medium land), Kaloran and Kledung Sub Districts (both are high land). Results showed that in general agricultural sector was an important as a source of income, in which contributed 30,6 % and 45 % for medium and high land respectively. For high land farmers, estate crops contributed the highest percentage (14%) followed by food crops (12%). The dominant estate crops were coffee, tobacco, coconut, clove, and cacao. Tobacco showed the highest revenue (Rp. 2,505 millions/household), even though also needed the highest production cost (Rp. 1,586 millions/household). In medium land, estate crops were in the fourth placed (5%) after livestock (9%), forestry (8%), and horticulture crops (6%). Dominant commodities were coffee, coconut, and clove. Marketing system was not different in both areas. Aside of coconut, estate crops was firstlyprocessed before being sold in village and sub district markets, in which was paid in cash. For tobacco commodity, traders were the source of price information, while for other commodities were neighbours/other farmers. Based on the analysis, efficiency could be increased through scaling up the farm size. Fanning consolidation was promising to be implemented